The evolution of traditional Korean interior designs and architecture under the Choson Period (1392-1910) - Yeri, Min; Mayo, Adelaida Villaraza (1996.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (Bachelor of Interior Design)--University of the Philippines Diliman
Keywords: Interior decoration -- Korea; Architecture, Domestic -- Korea; Design, Decorative -- Korea